Wolves eat dogs : a novel - Smith, Martin Cruz, 1942- (New York : Simon & Schuster, 2004)
In the wake of a businessman's suicide, Moscow detective Arkady Renko investigates secrets and international plots that may have driven him to his death, in a case that leads Renko to discover crimes in the area surrounding Chernobyl.
Map on lining papers.
Keywords: Renko, Arkady (Fictitious character) -- Fiction; Police -- Russia (Federation) -- Moscow -- Fiction; Billionaires -- Fiction; Chornobyl (Ukraine) -- Fiction; Moscow (Russia) -- Fiction; Mystery fiction